GAMBARAN KUALITAS BAKTERIOLOGIS AIR SUMUR GALI DI DESA KARANGANYAR KECAMATAN PURWANEGARA KABUPATEN BANJARNEGARA TAHUN 2021 - Dwi Atin Faidah; Sarmono (Unit Penelitian dan Pengabdian Masyarakat Politeknik Banjarnegara, 2021)
The people of Karanganyar Village use water resources with the majority of the water supply system using dug wells to meet their daily water needs. Dug wells must be supported by good conditions, which are in accordance with the requirements of healthy dug wells, which include physical conditions and the location of the well with pollutant sources. This study aims to describe the content of coliform bacteria of water in dug wells in Karanganyar Village, Purwanegara District, Banjarnegara Regency in 2021. This research is descriptive research with cross sectional approach. Total of 44 samples were taken using the proportional random sampling method in a cluster divided into 5 RWs in Karanganyar Village. The data used in this study are primary data obtained from observations and laboratory examinations. The results showed that from 44 samples of well water examined, 35 wells (79.55%) had met the health requirements in terms of coliform content. This is based on the quality standards established by the Regulation of the Minister of Health of the Republic of Indonesia No. 32 of 2017 concerning Water Health Quality Standards for Sanitary Hygiene, Swimming Pools, Solus per Aqua and Public Baths. The physical conditions such as the well wall (77.3%), well floor (63.6%), waste water channel (4.5%), well border (77.3%), well cover (72.7%). environmental cleanliness of the wells (86.4%), indicating that most of them have met the requirements. Coliform bacterial contamination of water in dug wells can be minimized by increasing public awareness and knowledge of the conditions of dug wells that are in accordance with the requirements of healthy dug wells which include the physical condition of the well and the location of the well with pollutant sources as well as continuing to improve environmental cleanliness around the dug well location.